Carbon Sequestration Potential of Common Access Resources in Arid and Semi-arid Regions of Northwestern India - Singh, G.; Bala, N.; Chaudhuri, K. K.; Meena, R. L. (Indian Forester, 2003)
A study was carried to observe the vegetation status of Common Access Resources (CARs) and carbon stock in some selected villages of 10 degraded sites in six ecozones namely degraded forest areas, land with scrub, gullies and ravines, degraded pastureland, salt land and sand desertic with objective of strategic planning to improve their productivity. High vegetation status in Gujarat resulted greater carbon stock compared to that in Rajasthan. Carbon in the form of vegetation biomass ranged from 1.96 to 2.83 Mg ha-1 in Gujarat and 0.24 to 1.73 Mg ha-1 in Rajasthan. Soil carbon was 3.60 to 6.38 Mg ha-1 compared to 1.13 to 5.18 Mg ha-1 in Rajasthan being lowest in the sandy area of Mokal and Ramgarh. The potential of carbon sequestration in the CARs has been worked out to he 6.13 Mg ha-1 yr-1. With this sequestration potential the CARs should be able to meet the local need for fuel fodder and small timber.